2019
DOI: 10.1177/0269881119826602
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive tianeptine treatment for bipolar disorder: A 24-week randomized, placebo-controlled, maintenance trial

Abstract: Objective: The purpose of this study was to assess the efficacy and tolerability of tianeptine as an adjunctive maintenance treatment for bipolar depression. Methods: This is a multicenter double-blind randomized placebo-controlled maintenance trial of adjunctive tianeptine 37.5 mg/day. Participants (n=161) had a Montgomery-Asberg Depression Rating Scale ⩾12 at entry. After eight weeks of open-label tianeptine treatment, those who responded to tianeptine (n=69) were randomized to adjunctive tianeptine (n=36)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
8
0
1
Order By: Relevance
“…The majority of studies included participants diagnosed with BD I/II as defined by the DSM-IV. Other studies included participants with BD I/II or BD-NOS, 24 , 36 BD as defined by the ICD-10, 25 , 30 BD with psychosis, 47 or restricted participants to BD-I 32 . The mood state of participants in the included studies was highly variable.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies included participants diagnosed with BD I/II as defined by the DSM-IV. Other studies included participants with BD I/II or BD-NOS, 24 , 36 BD as defined by the ICD-10, 25 , 30 BD with psychosis, 47 or restricted participants to BD-I 32 . The mood state of participants in the included studies was highly variable.…”
Section: Resultsmentioning
confidence: 99%
“…Adjunctive creatine monohydrate, high-and lowfrequency rTMS, infliximab, tianeptine and mifepristone were the interventions used (compared with TAU) in the 6 studies including patients with BD experiencing depressive episodes. [43][44][45][46][47][48] Across these studies, attention and social cognition were not measured, and only one evaluated problem-solving. Across the 5 domains included in the NMA (Supplementary Figure S3), none of the adjunctive therapies revealed significant benefits compared with TAU.…”
Section: Cognitive Outcomes For Network Development In Patients With Bd Experiencing Depressive or Manic Episodesmentioning
confidence: 99%
“…Other smaller RCTs found similar treatment efficacies between different adjunctive antidepressants (Frye et al, 2009;Kauer-Sant'Anna et al, 2019;Post et al, 2006;Sachs et al, 1994;Schaffer, Zuker, & Levitt, 2006;Shelton & Stahl, 2004), but those different antidepressants differed on rates of treatment-emergent manic switches (Post et al, 2006). Another recent study (N = 98) found that patients using adjunctive antidepressant drugs at discharge had lower rates of 12-month rehospitalization with no differences in mania hospitalization rates (Shvartzman et al, 2018).…”
Section: Two Large Studies From the Systematic Treatment Enhancementmentioning
confidence: 93%
“…Two large studies from the Systematic Treatment Enhancement Program for Bipolar Disorder trial investigated antidepressant use adjunctive to mood‐stabilizing treatment in a randomized (Sachs et al, 2007) and a nonrandomized fashion (Goldberg et al, 2007), finding no differences between antidepressant users and nonusers. Other smaller RCTs found similar treatment efficacies between different adjunctive antidepressants (Frye et al, 2009; Kauer‐Sant'Anna et al, 2019; Post et al, 2006; Sachs et al, 1994; Schaffer, Zuker, & Levitt, 2006; Shelton & Stahl, 2004), but those different antidepressants differed on rates of treatment‐emergent manic switches (Post et al, 2006). Another recent study ( N = 98) found that patients using adjunctive antidepressant drugs at discharge had lower rates of 12‐month rehospitalization with no differences in mania hospitalization rates (Shvartzman et al, 2018).…”
Section: Introductionmentioning
confidence: 94%